Superficial Macula Capillary Complexity Changes Are Associated With Disability in Neuromyelitis Optica Spectrum Disorders - Wei, Ruili; Xie, Jianyang; Wu, Huihui; He, Fangping; Meng, Fangxia; Liu, Jiang; Liang, Hui; Zhao, Yitian (Frontiers in Neurology, 2021)
Purpose: We examined the macular microvascular changes of the macula in neuromyelitis optica spectrum disorder (NMOSD) patients and its association with their disability and other clinical variables. Methods: Thirty-four NMOSD (13 patients without optic neuritis, NMOSD-NON, and 21 patients with a history of optic neuritis, NMOSD-ON) and 44 healthy controls (HCs) were included in the study. Optical coherence tomographic angiography (OCTA) was used to image the superficial (SCP), deep (DCP), and whole capillary plexus (WCP) in a 2.5-mm-diameter concentric circle [excluding the foveal avascular zone (FAZ)]. An algorithm (Dbox) was used to quantify the complexity of the three capillary layers by fractal analysis. We also evaluated the expanded disability scale status (EDSS). Results: Dbox values were significantly reduced in SCP (p < 0.001), DCP (p < 0.001), and WCP (p = 0.003) of NMOSD when compared with HCs. Dbox values were significantly reduced in NMOSD eyes with optic neuritis when compared with healthy controls (p < 0.001) and eyes without optic neuritis (p = 0.004) in the SCP. In the DCP, eyes with optic neuritis showed significantly reduced Dbox values when compared with eyes without optic neuritis (p = 0.016) and healthy controls (p < 0.001); eyes without optic neuritis showed significantly reduced Dbox values (p = 0.007) in the DCP when compared with healthy controls. A significant negative correlation (Rho = −0.475, p = 0.005) was shown between the superficial macula Dbox values and the EDSS in NMOSD patients. Additionally, a negative correlation (Rho = −0.715, p = 0.006) was seen in the superficial Dbox values in [e]eyes without optic neuritis and EDSS. Conclusions: Macular microvascular damage in the superficial plexus is associated with disability in NMOSD. Macular microvascular alterations arise independently of the occurrence of ON in NMOSD.